Two complementary analytical approaches to study odorant metabolism in the olfactory epithelium - Kornbausch, Nicole; Reynaud, Rémy; Büttner, Andrea; Steinke, Maria; Thomas-Danguin, Thierry; Loos, Helene; Heydel, Jean Marie (Food Chemistry, 2025)
Nasal odorant metabolism is essential for olfactory perception and detoxification, but its role in food aroma perception is not yet fully understood. Here, we developed an in vitro method based on solvent extraction and compared it to an ex vivo headspace sampling technique, both using rat olfactory epithelium. Metabolization of ethyl acetate, 2,3-pentanedione, benzaldehyde, and 2-furfurylthiol was investigated. All utilized odorants are commonly found in food and beverages, indicating a potential influence on food perception when metabolites influence the perception of their precursor. Experiments were conducted to evaluate derivatization catalyzed by metal ions, which is particularly interesting for canned food and beverages. The odor qualities of the metabolites were determined, and their potential influence on aroma perception was estimated. Our findings demonstrate the value of employing complementary methodologies to get comprehensive insights into metabolic activities in nasal epithelia, which contribute to achieve a full understanding of food aroma perception.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Complex formation; d-Orbitals; Gas chromatography-olfactometry; Gas chromatography–mass spectrometry; Nasal metabolism; Odor perception